Nepali Migrants Political Activisms in India and their Engagement with Homeland - Bashyal, Keshav (Journal of International Affairs, 2016)
Dominance of research on Nepalis migration to India is considers as ‘for livelihood’, ‘passage of rites’, ‘taken for granted’, more importantly ’tradition’ or ‘Kamaune’ for majority of Nepalis. Nepal is an oldest nation-state of South Asia and its democracy had been, for a number of times, suspended or dismissed which forced Nepali leaders to exile in India. It still continues in different ways. Nepal’s political development is directly or indirectly influenced by political activism in India. India has been important ‘space’ for Nepal’s political change and it also has been a place for migrant’s political activism since a long time.Out of several Nepali migrants’ organizations in India, some are active in transnational political mobilizations. This study will look into the concept, evolution and contemporary discourse of the political transnationalism. It examines in the framework of transnationalism; development process of major political parties in Nepal, and situation of Nepali migrant’s political activisms in India and their associations with homeland politics.